MLK Day and Racial Attitudes: Liking the Group More but Its Members Less. Issue 5 (12th February 2014) - Chopik, William J.; O'Brien, Ed; Konrath, Sara H.; Schwarz, Norbert
<x xml:space="preserve">Abstract</x> Intuition suggests that the Martin Luther King holiday (MLK Day) should improve racial attitudes toward African Americans. However, its influence may depend on whether African Americans are evaluated as a group or individually. In two studies, we assessed racial attitudes either on MLK Day or on a control day. As might be expected, participants had more sympathetic attitudes towards African Americans as a group on MLK Day compared to control days; however, they evaluated individual African American exemplars more negatively on MLK Day compared to control days, who presumably seemed worse by comparison to the eminent political figure.